جهود معلمة اللغة الربية في ترقية مهارة الكلام لدى طلاب مدرسة الإصلاح المتوسطة الإسلامية بوكيت تنجي - Inayati Arfanny (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
The problems of teaching the skill of speaking the Arabic language in Al-Islah Islamic Intermediate School in Bukittinggi are that the students face difficulties in pronouncing the Arabic language, the lack of seriousness of the students in participating in education, dictation, memorization and understanding of the Arabic language, in addition to the lack of interest and listening to the Arabic language, the teacher of the Arabic language, and the lack of Arabic language qualification. In this research, the researcher uses qualitative research, which is the research that makes the researcher as the main tool. Qualitative research produces and processes descriptive data, such as interviews and observations. Qualitative research is a method of directly observing and communicating with individuals to obtain the data the researcher is looking for. The results of the research are the efforts of the Arabic language teacher in promoting the speaking skill of the students of Al-Islah Intermediate Islamic School in Bukittinggi. The teacher pays attention to the grammar used by the students and listens to them as much as possible, and corrects the errors and arranges them correctly, so that they are easily accepted by the students and raise them. Paying attention to teaching it, providing motivation that can arouse students’ enthusiasm and interest, choosing the most appropriate method for the subject so that students can understand and understand teaching the Arabic language easily, combining the sciences of nobility and honor in teaching the Arabic language, providing easy examples to understand and implementing the teaching components regularly and conducting extracurricular education as described above.